Estudio y análisis de la autonomía de un banco de baterías (ups) implementado a un vehículo eléctrico tubular en la ciudad de Loja. - Cañar Calva, Lucio Aquilino (2018)
The present thesis has as a general objective to study and analyze the autonomy of a battery bank UPS (Uninterrupted Power System) implemented in a tubular electric vehicle, this type of transport is new in our environment, so that knowledge about autonomy of batteries are scarce. Higher energy density batteries have been developed, such as Lithium Ion batteries, which are therefore lighter in weight than nickel-cadmium, Nickel-Metal-Hydride and Acid-Lead. Some of the elements used in these batteries are toxic and harmful. For the environment, in addition, they continue to present problems of stability and price. For the elaboration of this special degree project, we will make use of the knowledge acquired during the race, referring to Uninterrupted Power Systems, maintenance, types and factors that limit the autonomy of the batteries. The methods used for the elaboration of this thesis were: analytic- synthetic, descriptive and deductive, since by means of these methods an autonomy analysis of the Uninterrupted Power Systems (UPS) implemented in a tubular electric vehicle was carried out, afterwards the advantages and disadvantages as well as the factors that limit the autonomy of said system, in addition, data such as distance traveled, battery life time, speed and consumption were obtained, these data being necessary to perform the field tests.